2020
DOI: 10.3389/fonc.2020.00730
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Capability of Next-Generation Sequencing Fusion Analysis in Identifying a Rare CASE of TRAF1-ALK-Associated Anaplastic Large Cell Lymphoma

Abstract: Background: Anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALCL) is a rare T-cell neoplasm, accounting for approximately 3% of adult non-Hodgkin lymphomas. Although NPM1 is the most common fusion partner with ALK, many others have been described, necessitating break-apart FISH studies for confirmation of the diagnosis. TNF receptor-associated factor 1 (TRAF1) is a rare ALK partner that is thought to confer a worse prognosis in patients. We describe the utility of next-generation sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…information on ALK partner genes, and could be helpful to elucidate their potential clinical relevance in large series of ALK-positive ALCL. 52,53 In agreement with previous studies, 9,10,21 ICO-Se1_CD28e2 fusion was found in 9 of 117 (7.7%) of PTCLs of TFH derivation (8 AITLs and 1 TFH-PTCL), but in only 1 of 46 PTCL-NOS and 1 of 8 ATLLs. The young age of patients with a CD28 fusion recently reported in ATLL patients 54 was not observed in this study (mean age, 64 years), and the patient harboring the double fusion ICO-Se1_CD28e2 associated with CTLA4e3_CD28e4 was 75 years old.…”
Section: Discussionsupporting
confidence: 89%
“…information on ALK partner genes, and could be helpful to elucidate their potential clinical relevance in large series of ALK-positive ALCL. 52,53 In agreement with previous studies, 9,10,21 ICO-Se1_CD28e2 fusion was found in 9 of 117 (7.7%) of PTCLs of TFH derivation (8 AITLs and 1 TFH-PTCL), but in only 1 of 46 PTCL-NOS and 1 of 8 ATLLs. The young age of patients with a CD28 fusion recently reported in ATLL patients 54 was not observed in this study (mean age, 64 years), and the patient harboring the double fusion ICO-Se1_CD28e2 associated with CTLA4e3_CD28e4 was 75 years old.…”
Section: Discussionsupporting
confidence: 89%
“…So far, there have been six reported cases of ALCL with a TRAF1 ‐ ALK fusion, including our case (Table S1). The average age was 43.3 years old and the age range was relatively narrow 9,11–14 . Skin involvement was mostly seen.…”
Section: Discussionmentioning
confidence: 99%